The The Impact of the Advanced Functional Literacy Program on the Entrepreneurial Abilities of Learners at PKBM Mentari in Malang Regency - Zilfah, Salsania (Learning Community : Jurnal Pendidikan Luar Sekolah, 2024)
The purpose of this study is to describe the impact of the advanced functional literacy program on the entrepreneurial abilities of learners at PKBM Mentari. The research utilizes a descriptive method with a qualitative approach. Data collection was carried out through observation, interviews, and documentation. To ensure the validity of the data, techniques such as prolonged engagement, persistent observation, and triangulation (both source and method triangulation) were employed. The data analysis process includes data collection, data reduction, data display, and conclusion drawing. The results of this study indicate that the advanced functional literacy program has a positive impact on the entrepreneurial abilities of learners, leading to business development. The program has resulted in increased knowledge and skills, enabling learners to innovate and create business opportunities, such as bamboo skewer production. This has led to an improvement in the quality of human resources. In terms of entrepreneurial abilities, there has been an increase in economic independence among participants. They have not only been able to create new income sources for themselves but have also contributed to the local economy by opening new business opportunities and providing employment.